La aristocracia altomedieval: legados historiográficos y tendencias de investigación - Mariel Pérez (Medievalista, 2014)
The aim of this paper is to review the bibliography in use on aristocracy of the High Middle Ages in order to present its central topics of analysis, its core problems and the main interpretive schemes that are crucial in this field of studies. This review will show that although the historiographical tradition inaugurated by Marc Bloch and Georges Duby actually inherited the topics and schemes from their predecessors –which led them to go deeply into the study of classical questions such as the transformations of its family structures–, in the last decades a number of new problems on medieval aristocracy emerged, as well as new frameworks of interpretation and methodological tools that are renewing and revitalizing these studies.